Perbandingan Uji Aktivitas Antibakteri Umbi Bawang Merah (Allium Cepa L) Dan Umbi Bawang Putih (Allium Sativum) Terhadap Pertumbuhan Bakteri Shigella Dysenteriae - Purnomo S, Fahrurrozi Hari; Fitrianingsih, Avin Ainur; Rahmah, Zainabur; Milliana, Alvi (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Background :Diarrhea is one of the causes of morbidity and mortality in infants and children around the world. One of the causes of diarrhea is Shigella sp bacteria or shigellosis. Nowadays, many antibiotics resistant to the Shigella sp bacteria are one example of chloramphenicol, so it is necessary to have other alternatives such as natural ingredients. Objective: Determine the activity of the red onion (Allium cepa L) and garlic (Allium sativum), which is known to possess antibacterial phytochemical compounds against the Shigella dysenteriae bacteria. Method: This research is a laboratory experimental study to determine antibacterial activity using the Kirby-Bauer or diffusion method of discs and to determine the presence of Minimum Inhibitory Concentration (MIC) and Minimum Bacterial Concentration (MBC). The study uses five treatments i.e., onion extracts and garlic extracts with a concentration of 30%, 40%, 50%, 60%, 70%, control positive (Ciprofloxacin), and negative control (aquadest). Results: Red onion diffusion has the best antibacterial activity at concentrations 70% while garlic has the best antibacterial activity at a concentration of 70%. In this study, there were no MIC and MBC. The MIC data analyzed with the crucial test of Kruskal-Wallis (p 0.05) i.e., in onion extract p = 0.003 and in garlic P = 0.003, which means significant. The MBC Data is analyzed by crucial test (P 0.05) in the onion extract p = 0.003 and on garlic p = 0.04. Conclusion : the disc diffusion and the MBC can be concluded that garlic extract can inhibit the growth of S. dysenteriae compared to red onion extracts. onion extracts).